Gender Based Violence in Fragile, Conflict, and Violence Situations : Five Key Questions to be Answered - Al-Tuwaijri, Sameera; Saadat, Seemeen (World Bank, Washington, DC, 2018)
The importance of addressing gender-based violence (GBV) in fragile, conflict, and violence (FCV) situations is increasingly recognized by countries and international humanitarian and development agencies. This note highlights the best practices in designing, implementing and evaluating a project involving addressing GBV in conflict and fragile situations. The note also provides an overview of the World Bank’s current engagement on GBV in fragile settings and internal resources available to TTLs.